Kelayakan Air Danau Toba di Wilayah Kabupaten Tapanuli Utara untuk Air Baku dan Wisata Air - Susanto, Joko Prayitno; Riyadi, Agung; Garno, Yudhi Soetrisno (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2021)
ABSTRACT In the area of North Tapanuli Regency, a special economic zone for Taman Bunga Tourism will be developed; so that in the future this area will require large amounts of clean water for consumption and water tourism facilities. In order to anticipate this water demand, a research was carried out to determine the feasibility of Lake Toba water in the North Tapanuli Regency area for drinking water raw water and water tourism infrastructure. This research was carried out with in-situ observations and water sampling for analysis in the laboratory according to the procedures of ISO 5667-6:2014 and ISO 5667-3:2012. This study suggests that Lake Toba water in the North Tapanuli Regency area is not yet suitable to be used as raw water for drinking water and water tourism infrastructure because it still has parameters of BOD, COD, Iron, and Barium that do not meet (exceed) the water quality criteria; according to Attachment Number VI to Government Regulation of the Republic of Indonesia Number 22 of 2021 concerning the Implementation of Environmental Protection and Management Keywords: Lake Toba, North Tapanuli, raw water, water recreation, water quality standard. ABSTRAK Di wilayah Kabupaten Tapanuli utara akan dikembangkan kawasan ekonomi khusus Pariwisata Taman Bunga, sehingga pada saatnya nanti kawasan ini akan memerlukan air bersih dalam jumlah besar untuk konsumsi dan sarana wisata air. Dalam rangka mengantisipasi kebutuhan air tersebut maka dilaksanakan penelitian untuk mengetahui kelayakan air Danau Toba di wilayah Kabupaten Tapanuli Utara untuk air baku air minum dan sarana prasarana wisata air. Penelitian dlaksanakan dengan pengamatan in-situ dan pengambilan sampel untuk analisis laboratorium sesuai prosedur ISO 5667-6:2014 dan ISO 5667-3:2012. Penelitian ini mengisaratkan bahwa air Danau Toba di wilayah Kabupaten Tapanuli Utara tidak layak untuk dijadikan air baku air minum dan sarana prasarana rekreasi air karena masih memiliki parameter BOD, COD, total fosfat, besi, dan barium yang tidak memenuhi nilai baku mutu yang berlaku. Untuk memanfatkan air Danau Toba di wilayah Kabupaten Tapanuli Utara diperlukan upaya penurunan konsentrasi parameter-parameter tersebut. Kata kunci: Danau Toba, Tapanuli Utara, bahan baku air, wisata air, baku mutu.